Beyond Lithium Ions: Research on Next-Generation Battery Technology (International Journal of Communication Systems and Network Technologies, 2024)
Technological developments in batteries are essential to meeting the rising energy needs of contemporary society. This study investigates the drawbacks of the present generation of lithium-ion batteries as well as the possibilities for their replacement. It covers the safety, energy density, and useful applications of solid-state batteries in particular, highlighting their potential. The obstacles that must be removed in order for these new technologies to become widely used are also covered in the article. In the end, it highlights how crucial it is to carry out more research on next-generation battery technologies in order to create a sustainable and energy-efficient future.
Keywords: Next-generation Batteries; Solid-state Batteries; Energy Storage; Lithium-ion; Energy Density